Job seekers, recruitment managers and employment agencies in Australia : a fractured triumvirate / P. J. Davis - Davis, P. J. (Faculty of Business Management, 2013)
The purpose of this paper is to explore the nature and extent of corporate recruitment managers‟ dissatisfaction with the services of private employment agencies they contract for search and selection help. The research finds that the form of recruitment managers‟ dissatisfaction relates to various aspects of service such as the quality of candidates recommended by agencies and communication. The relationship between the client (recruitment manager) and the provider (employment agency) is a further source of dissatisfaction. The extent of dissatisfaction varies between moderate and significant depending on the particular issue. The research also only canvasses the views of recruitment managers and not their agency counterparts and so only one perspective on the dynamics of the relationship is heard. The practical implications of the research is that there is significant opportunity for client and agency to improve their working relationship so that expectations are more clearly understood and communication is more productive.